ANALYSIS OF SONDONG FISHING AND DEVELOPMENT AT KOTA DUMAI - Megawati '; Irwandy Syofyan; Syaifuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in January 2016 at the Fish Landing Base (PPI) Dumai. This research purpose to know the feasibility and arrange the development direction sondong effort will be undertaken by fishermen Dumai. The method used is a survey method. The result of this study show sondong effort deserves to be developed, in the review of the feasibility of its development with a score of 3.25. Whereas the financial efforts of feasible developed by investment of Rp 99.818.000. Value of Benefit Cost Ratio (BCR) of 1,73, the Financial Rate of Return (FRR) 61,49% higher than the bank rate at 7,25%, and a payback period of capital (PPC) 1,63 years. Direction of business development sondong enough to be maintained, until there is a clear regulation of the government in Dumai about applicable regulations.Keywords: Sondong, Feasibility, investment, Development,Dumai PPI